2017
DOI: 10.1016/j.jvs.2017.07.064
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular stent grafting for ascending aorta diseases

Abstract: TEVAR in the ascending aorta seems to be safe and feasible for selected patients with various aortic diseases, although larger studies are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
75
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 40 publications
1
75
1
Order By: Relevance
“…The need for an alternative treatment becomes even more relevant when considering that more than 20% of the patients with type A aortic dissection (TAAD) are deemed inoperable [4] . In this context, ascending TEVAR could have potential advantages, such as absence of thoracotomy incision and need for partial or total extracorporeal circulatory support, as well as lower hospital morbidity rates and shorter length of hospital stay when compared to open surgery [5,6] . This was already well established on our initial experience [7] (Figures 1 and 2).…”
Section: Introductionmentioning
confidence: 99%
“…The need for an alternative treatment becomes even more relevant when considering that more than 20% of the patients with type A aortic dissection (TAAD) are deemed inoperable [4] . In this context, ascending TEVAR could have potential advantages, such as absence of thoracotomy incision and need for partial or total extracorporeal circulatory support, as well as lower hospital morbidity rates and shorter length of hospital stay when compared to open surgery [5,6] . This was already well established on our initial experience [7] (Figures 1 and 2).…”
Section: Introductionmentioning
confidence: 99%
“…For example, ascending aortic endovascular stent grafts have been used in select high-risk patients with Stanford Type A aortic dissection and five such cases were done at the highest volume hospital during the 4-year study period. 13 14 15 All five patients survived to hospital discharge and there were no strokes observed. For these cases, percutaneous common femoral arterial access is obtained and a 10-cm endovascular stent graft is brought retrograde via the descending thoracic aorta into the proximal ascending aorta near the intimal tear.…”
Section: Discussionmentioning
confidence: 92%
“…In a few cases, TEVAR has been performed for TAAD and other pathology affecting the ascending aorta. [15][16][17] However, these studies have reported limited indications for TEVAR in patients with TAAD. The procedure is challenging, and the results are uncertain.…”
Section: Discussionmentioning
confidence: 99%